STUDENTS’ MOTIVATION IN LEARNING ENGLISH AT SMP PLUS AMANAH ISLAMIC BOARDING SCHOOL TASIKMALAYA - Fajriati Safitri Hayati Kamila (Journal of Applied Linguistics (ALTICS), 2019)
AbstractThis research aims to investigate motivation and dominant motivation which students have at bilingual education system at SMP Plus Amanah Islamic Boarding School Tasikmalaya. This research employed a qualitative research design in the form of constructivist grounded theory. A modified questionnaire which was adopted from Gardner’s Attitude/Motivation Test Battery (AMTB) and structured interview questions were conducted. The results showed that the students have integrative and instrumental motivation but they tend to be slightly more instrumentally motivated.  The highest indicator items showed that students think that learning English can make them be a more knowledgeable person. Further, the student’s reason related to their motivation in learning English come up from the interview. It encompassed both integrative and instrumental motivation. For the reasons related to instrumental motivation, students learn English to get profitable career, to go traveling, to study or work abroad, to pass the test (school/job requirement), to participate in English competition, to understand English music, and to get high social status. Whilst for integrative motivation, they learn English to communicate with varied people from other countries, and they are interested in learning the language as well as the culture as their insight. Keywords: integrative motivation, instrumental motivation, bilingual education system, learning English